1997
DOI: 10.1046/j.1365-2222.1997.890900.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of inflammatory cell counts in asthma: induced sputum vs bronchoalveolar lavage and bronchial biopsies

Abstract: We conclude that the eosinophil counts in hypertonic saline-induced sputum from patients with asthma are related to those in bronchial wash and BAL and, to a lesser extent, with the counts in bronchial biopsies. This suggests that induced sputum can be used to monitor the presence and severity of airway inflammation in asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
75
1
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(89 citation statements)
references
References 36 publications
9
75
1
4
Order By: Relevance
“…The first is that sputum eosinophils is a sensitive indicator of airway inflammation which develops before clinical exacerbations of asthma [4]. The second is that from the two studies so far comparing sputum with biopsies, when sputum cell counts are normal, usually no eosinophils were found in the biopsies [16,17]. The evidence therefore suggests that in the assessment of the presence and type of airway inflammation, objective measurement by sputum cell counts is more accurate than indirect clinical assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is that sputum eosinophils is a sensitive indicator of airway inflammation which develops before clinical exacerbations of asthma [4]. The second is that from the two studies so far comparing sputum with biopsies, when sputum cell counts are normal, usually no eosinophils were found in the biopsies [16,17]. The evidence therefore suggests that in the assessment of the presence and type of airway inflammation, objective measurement by sputum cell counts is more accurate than indirect clinical assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Although sputum examination has not been established as the "gold standard" for sampling airway secretions, it provides cell counts qualitatively similar to those obtained by analysis of bronchial wash [14,15], lavage [14±18] and biopsy [16,17]. The authors considered that if the clinical assessment of the presence and type of airway inflammation compared well with the sputum cell counts, then this additional test may not be useful in practice.…”
mentioning
confidence: 99%
“…Sputum induction has been proposed as a safe, noninvasive and easily repeated method for monitoring inflammatory events in human airways, and the method of sputum induction has been validated in a number of studies and reported to be safe and reproducible [19±23]. Analysis of induced sputum results has shown them to correlate well with data obtained from bronchial wash and bronchoalveolar lavage [24,25]. In air pollution research, induced sputum has previously proved valuable in the evaluation of the airway effects of ozone [26] and nitrogen dioxide [27].…”
mentioning
confidence: 99%
“…23,24 However, when the eosinophil count was expressed as normal and abnormal values on the basis of the results from healthy controls, significant agreement could be found between sputum eosinophilia and presence of eosinophilic inflammation in bronchial mucosa. 23 Because, in this study, sputum eosinophil count was used to monitor the presence of eosinophilic inflammation in the bronchial mucosa of atopic asthmatics, we expressed the results of sputum eosinophil count in asthmatic patients as normal and abnormal values on the basis of data from healthy controls for statistical analysis.…”
Section: Discussionmentioning
confidence: 95%